Pembaruan Pemikiran Pada Masa Pemerintahan Umar Ibn Khattab Dan Implikasinya Pada Kemajuan Umat - Muthiullah Muthiullah; Insulinde Yuliati (AL-MUFASSIR, 2021)
Umar ibn Khattab is one of the four khulafa 'al-Rashidin who is famous for his stories of courage, firmness, and fierce impression. The identity of Umar's character is more popular than his political steps that are beneficial to Muslims. For this reason, this simple research tries to reveal the innovations and reforms of thought initiated by Umar al-Faruq, which include political, economic, and social-social ijtihad. In this research, the method used is a qualitative method by examining primary sources in the form of hadith atsar of the Companions, Date books, and secondary sources from journals, articles, and previous studies. The collected data will be analysed and described descriptively. Among the results of this research, it is known that Umar bravely broke down the old system while still maintaining the principles of the Quran and the Prophet. The reforms made by Umar were very significant for the development of Muslims, and their impact can still be felt today